2008
DOI: 10.1111/j.1349-7006.2008.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses intestinal polyp growth in ApcMin/+ mice

Abstract: Metformin is a biguanide derivative that is widely used in the treatment of diabetes mellitus. One of the pharmacological targets of metformin is adenosine monophosphate-activated protein kinase (AMPK). We investigated the effect of metformin on the suppression of intestinal polyp formation in Apc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(145 citation statements)
references
References 24 publications
5
130
0
4
Order By: Relevance
“…We showed that metformin suppressed the development of intestinal polyps in adenomatous polyposis coli (APC Min/+ ) mice, a murine model of familial adenomatous polyposis (16). Furthermore, we showed that metformin suppressed the azoxymethaneinduced formation of colorectal aberrant crypt foci (ACF) by activating AMPK (17).…”
Section: Introductionmentioning
confidence: 85%
“…We showed that metformin suppressed the development of intestinal polyps in adenomatous polyposis coli (APC Min/+ ) mice, a murine model of familial adenomatous polyposis (16). Furthermore, we showed that metformin suppressed the azoxymethaneinduced formation of colorectal aberrant crypt foci (ACF) by activating AMPK (17).…”
Section: Introductionmentioning
confidence: 85%
“…Another example of metformin action on the development of in situ tumors was observed in the Apc (Min/+) mice models. Administration of metformin at 250 mg/kg in the diet significantly reduced the number of large polyps (41). Finally, we and others showed that metformin efficiently inhibits tumor growth in prostate, colon, or lung cancer cell xenografts (25,31,42).…”
Section: Preclinical Studies and Antitumor Growth Action Of Metforminmentioning
confidence: 95%
“…For example, it has been shown that metformin suppresses polyp formation in ApcMin/ þ mice (Tomimoto et al, 2008), inhibits in vivo growth of p53 null cancers (Buzzai et al, 2007), attenuates tumorigenesis in phosphatase and tensin homolog-deficient mice (Huang et al, 2008) and slows proliferation of triple-negative breast cancer cells (Liu et al, 2009); however, these studies did not investigate the anti-neoplastic effects of metformin in the context of variation of dietary energy intake or insulin levels. This issue is critical as all epidemiological evidence for an anti-neoplastic action of metformin is derived from type II diabetic patients and metformin has important endocrine effects at the whole organism level in the setting of type II diabetes, apart from any direct effects on neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%